2013
DOI: 10.1053/j.jfas.2012.10.011
|View full text |Cite
|
Sign up to set email alerts
|

A Review of 105 Consecutive Uniport Endoscopic Plantar Fascial Release Procedures for the Treatment of Chronic Plantar Fasciitis

Abstract: Level of Clinical Evidence: 3 Keywords: calcaneus chronic inflammation endoscopy heel pain plantar fasciitis surgery a b s t r a c t Plantar fasciitis is a common cause of heel pain in the U.S. Army soldier, resulting in a significant loss of man hours. Given the heavy operations tempo of the U.S. military, successful treatment options need to be considered and used as quickly as possible. Plantar fasciitis can be successfully treated in up to 90% of patients using conservative measures. Operative intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 9 publications
1
23
0
1
Order By: Relevance
“…In contrast, patients with lower weights and BMIs had greater postoperative pain relief [14], and those with a BMI > 27 kg/m 2 had less favorable results [29]. Otherwise, older age seems a protective factor for an early postoperative return to work [14,15]. In our patients, the non-obese group showed significantly earlier pain reduction and functional improvement than did the obese group.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…In contrast, patients with lower weights and BMIs had greater postoperative pain relief [14], and those with a BMI > 27 kg/m 2 had less favorable results [29]. Otherwise, older age seems a protective factor for an early postoperative return to work [14,15]. In our patients, the non-obese group showed significantly earlier pain reduction and functional improvement than did the obese group.…”
Section: Discussionmentioning
confidence: 50%
“…In the endoscopic release of plantar fascia, obesity was reported not to negatively affect the outcome [28]. In contrast, patients with lower weights and BMIs had greater postoperative pain relief [14], and those with a BMI > 27 kg/m 2 had less favorable results [29]. Otherwise, older age seems a protective factor for an early postoperative return to work [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13][14][15][16][17] The technique has been modified to remove the plantar calcaneal spur 18 and plantar calcaneal bursa. 19 However, the deep abductor hallucis fascia cannot be released by the reported techniques of endoscopic plantar fascia release.…”
Section: Discussionmentioning
confidence: 99%
“…However, surgery can be considered for a small subgroup of carefully selected patients with persistent, severe symptoms despite nonoperative intervention for !6 to 12 months. A previous study showed that patients with a high body mass index could experience greater pain after surgery than leaner patients (27). The surgical procedures used for plantar fasciitis have included variations of open or closed partial or complete plantar fascia release with or without calcaneal spur resection, excision of abnormal tissue, and nerve decompression (28,29).…”
Section: Discussionmentioning
confidence: 99%